Hydrothermal multivariable approach. Full-scale feasibility study - Pérez-Elvira, Sara I.; Fernández-Polanco, Fernando; Fernandez-Polanco, María; Rodriguez, Pilar; Rouge, Philippe (Electronic Journal of Biotechnology, 2008)
A process configuration combining thermal hydrolysis (TH) and anaerobic digestion (AD) of sludge has been studied with the objective of analysing the feasibility of the technology for full scale installations. The study has been performed through pilot scale experiments and energy integration considerations, and a scheme of the most profitable option is presented: thermal hydrolysis unit fed with 7% total solids (TS) secondary sludge, anaerobic digestion of the hydrolysed sludge together with fresh primary sludge, and a cogeneration unit to produce green electricity and provide hot steam for the thermal hydrolysis process. From a technical and practical point of view, the process scheme proposed is considered to be feasible. Based on the results of the pilot plant performance and the laboratory studies, the process has proven to operate successfully at a concentration of 7-8% TS. After the thermal hydrolysis, sludge viscosity becomes radically smaller, and this favours the digesters mixing and performance (40% more biogas can be obtained in nearly half the residence time compared to the conventional digestion). From an economic point of view, the key factors in the energy balance are: the recovery of heat from hot streams, and the concentration of sludge. The article presents the main energy integration schemes and defines the most profitable one: an energetically self-sufficient process, with a cogeneration unit. The scheme proposed has proven to need no additional energy input for the sludge hydrolysis, generates more that 1 MW green electricity (246 kW surplus with respect to the conventional process), and produces 58% less volume of Class A biowaste. The study and balances here presented set the basis for the scale-up to a demonstration plant (hydrolysis + anaerobic digestion + cogeneration unit).